Intrauterine transfusion in hydropic fetuses: An outcome analysis - Rashmi Parashar; Archana Bajpayee; Puneeth Babu Anne (Asian Journal of Transfusion Science)
The objective of this study is to determine the perinatal outcome in pregnancies with hydropic fetuses. The study was a retrospective evaluation of data on intrauterine transfusion (IUT) done in hydropic fetuses for correction of severe anemia from December 2017 to August 2021 in AIIMS Jodhpur. The retrospective case series involves five cases that underwent IUT for severe fetal anemia. All had a sign of hydrops at the time of presentation. Out of five cases, four were of alloimmunized pregnancies while one was of hydrops fetalis secondary to parvovirus infection. The presence of severe hydrops at the time of presentation is a poor prognostic factor affecting fetal survival post-IUT therapy.